Photoplethysmogram beat detection using Symmetric Projection Attractor Reconstruction - Pettit, Callum; Charlton, Peter H.; Aston, Philip J. (Frontiers in Physiology, 2024)
Many methods have been proposed to detect beats in photoplethysmogram (PPG) signals. We present a novel method which uses the Symmetric Projection Attractor Reconstruction (SPAR) method to generate an attractor in a two dimensional phase space from the PPG signal. We can then define a line through the origin of this phase space to be a Poincar é section, as is commonly used in dynamical systems. Beats are detected when the attractor trajectory crosses the Poincar é section. By considering baseline drift, we define an optimal Poincar é section to use.The performance of this method was assessed using the WESAD dataset, achieving median F 1 scores of 74.3% in the Baseline phase, 63.0% during Stress, 93.6% during Amusement, and 97.7% during Meditation. Performance was better than an earlier version of the method, and comparable to one of the best algorithms identified in a recent benchmarking study of 15 beat detection algorithms. In addition, our method performed better than two others in the accuracy of the inter-beat intervals for two resting subjects.